The Effect of COVID on Child Maltreatment: A Review - Rokach, Ami; Chan, Sybil (Journal of Psychology and Psychotherapy Research, 2022)
This article addresses child maltreatment during the period where COVID-19 entered our lives in 2020. Repeated lockdowns kept children at home, away from school, from their support systems, and from their daily routines. Parents have also been plagued by the economic challenges associated with remote living. This not only places additional stress on the quality of their livelihoods but also, renders their caregiving duties as exceedingly onerous. This article explores the reasons that ACEs increased during that time, and highlights what can parents, teachers, and the educational system do about it.